Exploring the Linguistic Patterns of Gratitude: A Comparative Analysis of Acknowledgments in Philosophy PhD Theses - Fatma Yuvayapan; Hayriye Bilginer (English Studies at NBU, 2024)
Acknowledgments as expressions of gratitude are not only mere formalities in academia but also represent heartfelt attempts by researchers to acknowledge the support that shaped their academic journeys. They are a specific academic genre in which personal texts are produced as a part of academic genres such as theses or books. Hence, a systematic understanding of the linguistic features of this specific genre may contribute to the literature on academic writing. Comparing expressions of gratitude across English, German, and Turkish L1 academic contexts, this study presents a detailed picture of linguistic patterns in Ph.D. thesis acknowledgments in the field of Philosophy. We found that thanking for academic purposes was the main reason for gratitude in the three cultures. Our analysis also revealed the influence of cultural and linguistic nuances on the syntactic patterns of gratitude in the three contexts. We concluded that while acknowledgments remain deeply personal and emotionally charged, they adhere to genre-specific encoding patterns and share common lexical preferences, which require explicit instruction in academic writing courses.